First records of myxomycetes from Bathurst Island (one of the Tiwi Islands) in the Northern Territory, Australia. (27th July 2020) - White, Mary A.; Elliott, Todd F.; Kennedy, Brooke P. A.; Stephenson, Steven L.
Abstract: Myxomycetes, also known as plasmodial slime moulds or myxogastrids, are a widespread but often overlooked group of amoeboid eukaryotes. There are still many regions where they have been poorly studied or entirely overlooked. In an effort to more completely document myxomycete diversity and distribution in Australia, we provide the first report of myxomycete occurrence on the Tiwi Islands. Four of the species recorded from Bathurst Island are new records for the Northern Territory. This natural history note is based on 50 moist chamber cultures prepared with substrate samples collected on Bathurst Island. These cultures yielded 28 specimens representing a total of twelve species in eight genera.